Does Central Bank Staff Beat Private Forecasters? - Alexander Jung; Makram El-Shagi; Sebastian Giesen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper assesses the relative performance of central bank staff forecasts and of private forecasters for inflation and output. We show that the Federal Reserve (Fed), and less so the European Central Bank (ECB), has a significant information advantage concerning inflation and output forecasts. Using recently developed tests for conditional predictive ability and forecast stability for the US, we find that the driving forces behind the narrowing of the information advantage of Greenbook forecasts have coincided with the Great Moderation.
Keywords: C53; E37; E52; 330